Scope Pembelajaran Pendidikan Agama Islam Di Sekolah Dan Madrasah - Nurdin Nurdin; Armia Armia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The problems in PAI relating to the learning process, it cannot be separated from three fundamental reasons, namely the orientation of PAI learning which relies more on cognitive aspects only; education system that is less systematic and less integrated; Finally, the evaluation carried out is equated with other lessons, namely only on the cognitive aspect. By using library research, a study of teacher and writer lesson plans found that the scope of Islamic Religious Education learning in schools was designed within the scope of Islamic Religious Education subject matter in schools including; AlQur'an/Hadith, Aqidah/Akhlak, Fiqh/Worship and Dates and Islamic Culture are presented in 3 hours face-to-face every week. There are so many material demands that have not been able to be completed optimally because educators are still carrying out conventional tasks, so that the effectiveness of the educational process or the development of curriculum materials in PAI learning has not been fully achieved. While the scope of Islamic Religious Education in madrasas includes subjects; Aqidah Akhlak, Qur'an and Hadith, Fiqh and Islamic Cultural History, each subject has separate face-to-face hours. However, all of these subjects have not been able to be presented effectively and optimally.